2022
DOI: 10.1177/09636897221082687
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells Overexpressing HIF-1α Prevented the Progression of Glucocorticoid-Induced Avascular Osteonecrosis of Femoral Heads in Mice

Abstract: Glucocorticoid (GC)-induced avascular osteonecrosis of femoral head (AOFH) is a devastating complication, and no cures are currently available for it. Previous studies have demonstrated that implantation of bone marrow mesenchymal stem cells (BMMSCs) may prevent the progression of pre-collapse AOFH. Based on previous observations, we hypothesized that GCs induce AOFH via the COX-2 (cyclooxygenase-2)–PGE-2 (prostaglandin E2)–HIF-1α (hypoxia-inducible factor-1α) axis, and that modification of BMMSCs may improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Xu et al [ 39 ] demonstrated that over-expressed HIF-1α resisted Dex-induced apoptosis in a hypoxic environment. Implantation of bone marrow mesenchymal stem cellsoverexpressing HIF-1α into femoral heads of GIONFH mice significantly reduced osteonecrotic areas and enhanced bone repair [ 40 ]. Sun et al [ 41 ] found that Dex induces osteoblast apoptosis via theFoxO signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [ 39 ] demonstrated that over-expressed HIF-1α resisted Dex-induced apoptosis in a hypoxic environment. Implantation of bone marrow mesenchymal stem cellsoverexpressing HIF-1α into femoral heads of GIONFH mice significantly reduced osteonecrotic areas and enhanced bone repair [ 40 ]. Sun et al [ 41 ] found that Dex induces osteoblast apoptosis via theFoxO signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al 17 figured out that COX-2 enhanced osteogenic activity in rats. Zhang et al 18 reported that glucocorticoid induced ONFH via the COX-2-PGE-2 (prostaglandin E2)-HIF-1α (hypoxia-inducible factor-1α) axis. They found that dexamethasone repressed COX-2 expression, thereby reducing HIF-1α expression in femoral heads.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 2D skin multitype cells are cultured in the laboratory and they tend to adhere to flat surfaces. This traditional culture method depletes growth media and metabolic wastes, which may result in cell death, nutrient depletion, and damage to the environment in which they are grown, thus preventing complete cell function 12 – 16 . It also does not adequately consider the influence of the three-dimensional (3D) microenvironment under natural physiological conditions on its internal response and affects dose effectiveness and dose toxicity prediction data 17 .…”
Section: Introductionmentioning
confidence: 99%